8. IMPACT OF ETHYL EXTRACTS OF THE LEAVES OF HEXALOBUS MONOPETALUS (ANNONACEAE) ON DIURESIS AND SALIDIURESIS IN WISTAR STRAIN RATS - BEHANZIN, GBÉSSOHÈLÈ JUSTIN; Akotegnon, Rodrigue (My University, 2018)
Our study on the treatment of pathologies related to waste disposal through water by urinary excretion focused on the ethyl extract of the dry leaves of Hexalobus monopetalus. The evaluation of the diuretic and salidiuretic properties of this extract is an analytical, prospective and transverse study. Its objective is to analyze the chemical composition of the leaves and to assess the diuretic and salidiuretic activities of the ethyl extract. The method used to analyze theleaves used is phytochemical screening. The aqueous extract is administered by gavage to wistar strain rats. The volume of urine excreted and the quantity of ions are determined on the measuring cylinder by ion spectrophotometry. The results show that the urine of the rats has a pH of between 9.3 and 9.15. The baseline diuresis in six (6) hours is 5mL. Significant diuretic activity (177%, 262.5% and 203%) was observed in rats treated with 67.5 doses, respectively; 135 and 202.5 mg / kg / bw of the Hexalobus monopetalus ethyl extract compared to 200% in furosemide-treated rats at 20 mg / kg. The saluretic activity of this extract is ethyl of 10.34 at a dose of 67.50 mg / kg of the extract, the same value for the furosemide at 20 mg / kg and 4.05 for the distilled water. The 135mg / kg dose of the extract is the best diuretic activity (262.5%) and the dose 67.5 mg / kg / bw of the extract is the best in terms of salidiuretic activity (10, 34 ± 1.5). The ethyl extract of the leaves of the Hexalobus monopetalus helps eliminate blood creatinine and blood does not influence the balance of ions such as calcium, potassium, sodium and chlorine e. However the extract prevents a good elimination of urinary urea through the kidney which would result from an organic deficiency
Keywords: Hexalobus monopetalus; diuretic and salidiuretic activities; ethyl extract; wistar rats.